Adjustment for growth : the African experience - Hadjimichael, Michael T...[et al] (IMF WashingtonUS, 1996)
Presents a cross-country analysis which assess empirically the role of public policies in stimulating private saving and investment in sub-Saharan Africa in 1986-92. Supplies case studies which discuss the experiences of three countries during periods of adjustment efforts: Ghana in 1983-91, Senegal in 1978-93, and Uganda in 1987-94.